New fluorescently labeled auxins exhibit promising anti-auxin activity - Bieleszová, Kristýna; Pařízková, Barbora; Kubeš, Martin; Husičková, Alexandra; Kubala, Martin; Ma, Qian; Sedlářová, Michaela; Robert, Stéphanie; Doležal, Karel; Strnad, Miroslav; Novák, Ondřej; Žukauskaitė, Asta (New biotechnology, 2019)
The plant hormone auxin is a key player in the regulation of plant growth and development. Despite numerous studies devoted to understanding its role in a wide spectrum of physiological processes, full appreciation of its function is linked to a comprehensive determination of its spatio-temporal distribution, which plays a crucial role in its mode of action. Conjugation of fluorescent tracers to plant hormones enables sensitive and specific visualization of their subcellular and tissue-specific localization and transport in planta, which represents a powerful tool for plant physiology. However, to date, only a few fluorescently labeled auxins have been developed. We report the synthesis of four novel fluorescently labeled derivatives of indole-3-acetic acid (IAA) in the form of a conjugate with a nitrobenzoxadiazole (NBD) fluorophore together with validation of their biological activity. These compounds, unlike other previously reported auxins fluorescently labeled at N1 position (nitrogen of the indole ring), do not possess auxin activity but rather show dose-dependent inhibition of auxin-induced effects, such as primary root growth inhibition, root hair growth and the auxin reporter DR5::GUS expression. Moreover, the study demonstrates the importance of the character of the linker and optimal choice of the labeling site in the preparation of fluorescently labeled auxins as important variables influencing their biological activity and fluorescent properties.
Keywords: DR5::GUS; Arabidopsis; kořeny rostlin; Anti-auxin; spektrofotometrie; Indole-3-acetic acid (IAA); Molecular Structure; kyseliny indoloctové; molekulární struktura; Indoleacetic Acids; Spectrophotometry; Fluorescent Dyes; Plant Roots; regulátory růstu rostlin; Fluorescent labeling; Plants, Genetically Modified; fluorescenční barviva; Spectrometry, Fluorescence; fluorescenční spektrometrie; geneticky modifikované rostliny; Plant Growth Regulators; Biological activity